A safety evaluation of mixed human milk oligosaccharides in neonatal farm piglets. (24th November 2020) - Hanlon, Paul R
Human Milk Oligosaccharides (HMOs) are the third most abundant, solid component of human milk after lactose and fat. As novel processes are developed to cost-effectively produce commercial volumes of these oligosaccharides, they are becoming more common components of infant formulas worldwide. The study evaluated the safety of a novel mixture of HMOs in a neonatal piglet model with the objective of identifying potential effects during the sensitive, preweaning developmental stage of life. The mixture of HMOs (HMO MIX 1) was composed of 2′-fucosyllactose (2′-FL), 3-fucosyllactose (3-FL), lacto-N-tetraose (LNT), 3′-sialyllactose (3′-SL), and 6′-sialyllactose (6′-SL), and was administered to 2-day old piglets at either 5.75 or 8.0 g/L for a period of 21 days. Piglets in the 5.75 and 8.0 g/L HMO MIX 1 dosing groups did not exhibit differences in body weight, food consumption, or feed efficiency. Analysis of clinical chemistry parameters on Study Day 7 and Study Day 21 did not demonstrate any effects that could be attributed to HMO MIX 1, nor were there any findings in organ weight, macroscopic, or microscopic inspection of tissues that could be attributed to this oligosaccharide blend. Therefore, since administration of HMO MIX 1 in a liquid diet up to 8.0 g/L resulted in no toxicologically-relevant effects in comparison with animals fed a control diet, this study supports the safety of this ingredient for addition to infant formula products.